2019
DOI: 10.1186/s12913-019-4044-y
|View full text |Cite
|
Sign up to set email alerts
|

The politics and ethics of hospital infection prevention and control: a qualitative case study of senior clinicians’ perceptions of professional and cultural factors that influence doctors’ attitudes and practices in a large Australian hospital

Abstract: Background Hospital infection prevention and control (IPC) programs are designed to minimise rates of preventable healthcare-associated infection (HAI) and acquisition of multidrug resistant organisms, which are among the commonest adverse effects of hospitalisation. Failures of hospital IPC in recent years have led to nosocomial and community outbreaks of emerging infections, causing preventable deaths and social disruption. Therefore, effective IPC programs are essential, but can be difficult to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
51
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 57 publications
6
51
2
Order By: Relevance
“…In an ED where there are numerous 'leaders', different role models and aberrant behaviour can impact negatively on the IPC culture of the department. Participants identified a lack of positive role modelling and leadership which has been shown elsewhere to influence individual behaviour towards PPE [26,47,48]. In contrast to our findings, a recent qualitative study that utilised focus groups with nurses and assistants, reported a positive peer culture for encouraging respirator mask use [49].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In an ED where there are numerous 'leaders', different role models and aberrant behaviour can impact negatively on the IPC culture of the department. Participants identified a lack of positive role modelling and leadership which has been shown elsewhere to influence individual behaviour towards PPE [26,47,48]. In contrast to our findings, a recent qualitative study that utilised focus groups with nurses and assistants, reported a positive peer culture for encouraging respirator mask use [49].…”
Section: Discussioncontrasting
confidence: 97%
“…One barrier to optimal mask use demonstrated in our research was the strong personal belief about PPE use of some senior medical staff, which overrode IPC policy. This is reflective of a recent study which found that the clinical autonomy of doctors was a significant factor in their IPC practice [47]. In an ED where there are numerous 'leaders', different role models and aberrant behaviour can impact negatively on the IPC culture of the department.…”
Section: Discussionmentioning
confidence: 70%
“…Organisations also have a responsibility to ensure that senior medical staff ful l their accepted professional responsibility to model appropriate clinical practice, including correct PPE use (41). Nevertheless, we suggest that enabling re exivity-in-practice, using methods such as video-re exive ethnography, may not only identify these issues, but also allow clinicians to devise creative and sustainable strategies to address them, as they have previously in similar acute care settings (34,42).…”
Section: Discussionmentioning
confidence: 93%
“…For instance, ensuring that appropriate PPE stocks are available, providing physical locations for staff to place items for temporary safekeeping, encouraging use of fob (rather than wrist-) watches for use in clinical assessment. Organisations also have a responsibility to ensure that senior medical staff ful l their accepted professional responsibility to be role models of appropriate clinical practice, including correct PPE use (35).…”
Section: Discussionmentioning
confidence: 99%